+0  
 
+1
41
2
avatar+5 

x+y+3z=10,\:-4x+3y+5z=7

 Apr 20, 2021
 #2
avatar+108 
0

Get y by itself in the first equation

 

x + y + 3z = 10      →   y =  10 - x - 3z

 

Substitute this into the second equation and simplify:

 

-4x + 2y +5z = 7    →   -4x + 2(10 - x - 3z) + 5z = 7   →   -4x + 20 -2x - 6z + 5z  = 7  →  -6x - z = -13  →

 

6x + z  = 13

 

So we have this system:

 

k*x + z = 3

 

6x + z = 13 

 

And notice that, if k =6, we would have this system:

 

6x + z  = 3      and

 

6x + z  = 13       but this is impossible, because two things added together can't possibly have two different outcomes 

 

So....as geno found, when k = 6, the system has no solution...!!!

 

WORD OF CPhill

 Apr 20, 2021

16 Online Users